2020
DOI: 10.2478/ebtj-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Achillea millefolium essential oil compounds and biological effects on cervix cancer HeLa cell line

Abstract: Yarrow essential oil is used in complementary and alternative therapy for several diseases. Biological effects of essential oils span various cells and microorganisms. The aim of this study was to investigate the effects of different concentrations of the essential oil obtained from the yarrow plant (Achillea millefolium) on HeLa (CCL-2) cells. The components of the essential oil were studied by means of GC-MS analysis. Out of 10 determined compounds in the essential oil; 1,8-Cineole, Camphor, Beta-eudesmol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These applications are mentioned in other traditional medicine as well (5), corroborated by experiments (6). Modern scientific investigations show that it possesses anti-inflammatory (7), antioxidant and antibacterial activities (8,9), as well as antican- Original scientific paper 124 cer properties (10). The aim of this investigation is to determine essential oil composition of A. millefolium sensu lato from Mt Rtanj and to develop a QSRR model for predicting the retention times of chemical compounds from the essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…These applications are mentioned in other traditional medicine as well (5), corroborated by experiments (6). Modern scientific investigations show that it possesses anti-inflammatory (7), antioxidant and antibacterial activities (8,9), as well as antican- Original scientific paper 124 cer properties (10). The aim of this investigation is to determine essential oil composition of A. millefolium sensu lato from Mt Rtanj and to develop a QSRR model for predicting the retention times of chemical compounds from the essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the effects of different concentrations of the essential oil of A. millefolium on HeLa (CCL‐2) cells. They reported that the essential oil had a high repressive effect on HeLa cells, decreased their proliferation, and prevented the increase in the number of cells [4] . It is noteworthy that the cytotoxic activity of A. millefolium was seen in previous studies, but we compared cytotoxic activity of A. millefolium essential oil in free, nano‐liposomal, and nano‐niosomal form.…”
Section: Resultsmentioning
confidence: 90%
“…They reported that the essential oil had a high repressive effect on HeLa cells, decreased their proliferation, and prevented the increase in the number of cells. [4] It is noteworthy that the cytotoxic activity of A. millefolium was seen in previous studies, but we compared cytotoxic activity of A. millefolium essential oil in free, nano-liposomal, and nano-niosomal form. In our study, there was a significant difference between the toxicity of encapsulated essential oil and free essential oil in terms of viability at concentrations of 15, 30, 60, 125, and 250 μg/ml (P < 0.05).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Achillea millefolium L. (AM) belongs to the Asteraceae family and it is prescribed as a complementary and alternative therapy for many diseases, including cancer, cystitis, diabetes mellitus, for example (MB et al., 2020). AM is a potential therapeutic agent because of its many different chemical constituents such as flavonoids, phenols, alkamides, coumarins, terpenoids, sterols and glucoside.…”
Section: Introductionmentioning
confidence: 99%